THE IMPACT OF THE DEVELOPMENT OF E-COMMERCE ON THE RETAIL SERVICES MARKET - Artikov Zokir Sayfiddinovich (Journal of Applied Science and Social Science, 2026)
This study analyzes the impact of the development of e-commerce on the retail services market. It examines structural changes in retail systems, the transformation of consumer behavior, and the increasing role of digital platforms in global trade. The research highlights how e-commerce improves economic efficiency through cost reduction, supply chain optimization, and expanded market access for businesses, particularly small and medium-sized enterprises. It also discusses challenges such as employment restructuring, regulatory adaptation, data protection issues, and market concentration in digital platforms.